APLIKASI WEBSITE SISTEM INFORMASI AKUNTANSI MANAJEMEN KEUANGAN TALANG GANTUNG ADVENTURE (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Talang Gantung Adventure is engaged in learning services outside the classroom or open air which is usually called outbound. In carrying out operational activities there are always financial transactions. However, in Talang Gantung Adventure, financial management still uses manual recording, which is recording in a ledger. Financial reports to the owner of the Talang Hang Adventure are performed using Microsoft Excel. Manual Financial Management results in vulnerability in storing financial data and is difficult to find data so that it has not been effective and has difficulties in preparing financial reports.Based on this research the authors designed and made a financial management accounting information system website application Talang Gantung Adventure. The purpose of making this system is to facilitate the recording of financial transactions, facilitate the search for data and be safer in storing Talang Gantung Adventure data storage, and to produce financial reports that are easily reported to the owner of Talang Gantung Adventure wherever and whenever.